Photobiomodulation by low-level laser therapy in patients with obstructive sleep apnea: Study protocol clinical trial (SPIRIT compliant) - de Camargo, Fernanda Cristina Ferreira (Medicine (Baltimore), 2020)
Obstructive sleep apnea (OSA) increases morbidity and mortality and it is associated with an increased cardiovascular risk. The gold standard treatment for OSA is positive airway pressure therapy (CPAP). However, it is an expensive treatment and several patients do not adapt to CPAP. GOAL: The researchers will verify the effects of low-level laser therapy (LLLT) on OSA, when applied to the soft palate and on the tongue base. METHODS: The researchers will select individuals of both sexes aged 30 to 60 years old who are sedentary and that present a high risk of OSA by the Berlin questionnaire. The evaluations pre and post interventions will be polysomnography; anthropometric and body composition measurements (Bioimpedance); metabolic syndrome risk factors (International Diabetes Federation); physical capacity (VO(2) peak at the cardiopulmonary exercise test, CPET); endothelial function (flow-mediated dilatation, FMD); autonomic control (heart rate variability and sympathovagal balance). Those diagnosed with moderate and severe OSA (apnea/hypopnea index, AHI ≥15 events/h) will be invited to participate in the study and they will be randomized into 2 groups: LLLT treatment or placebo (C). The LLLT group will receive applications at 8 points on the soft palate and on the base of the tongue for 8 seconds for each point. The applications of LLLT will occur twice a week, with a minimum interval of 2 days between the applications for 2 months, when using a Therapy Plus NS 13678 Laser. The C group will have similar applications, but with the device turned off. EXPECTED RESULTS: In the individuals with OSA, photobiomodulation through LLLT will decrease the AHI. Additionally, when LLLT is applied in the oral cavity, a highly vascularized region, this may cause improvements in the vascular function and in the autonomic and hemodynamic control. ETHICS AND DISSEMINATION: This protocol was approved by the Research Ethics Committee of the Nove de Julho University, São Paulo, Brazil, on the date of March 11, 2019 (CAAE: 06025618.2.0000.5511 - Acceptance Number: 3.191.077). This trial has been registered with the Brazilian Registry of Clinical Trials (REBEC TRIAL RBR-42v548). This study is not yet recruiting. Issue date: November 4, 2019.